Altered Mycobacterium tuberculosis Cell Wall Metabolism and Physiology Associated With RpoB Mutation H526D - Campodónico, Victoria L.; Rifat, Dalin; Chuang, Yu-Min; Ioerger, Thomas R.; Karakousis, Petros C. (Frontiers in Microbiology, 2018)
Background: Mycobacterium tuberculosis (Mtb) rpoB mutations are associated with global metabolic remodeling. However, the net effects of rpoB mutations on Mtb physiology, metabolism and function are not completely understood. Based on previous work, we hypothesized that changes in the expression of cell wall molecules in Mtb mutant RpoB 526D lead to changes in cell wall permeability and to altered resistance to environmental stresses and drugs. Methods: The phenotypes of a fully drug-susceptible clinical strain of Mtb and its paired rifampin-monoresistant, RpoB H526D mutant progeny strain were compared. Results: The rpoB mutant showed altered colony morphology, bacillary length and cell wall thickness, which was associated with increased cell wall permeability and susceptibility to the cell wall detergent SDS after exposure to nutrient starvation. Relative to the isogenic rifampin-susceptible strain, the RpoB H526D mutant showed altered bacterial cellular metabolic activity and an 8-fold increase in susceptibility to the cell-wall acting drug vancomycin. Conclusions: Our data suggest that RpoB mutation H526D is associated with altered cell wall physiology and resistance to cell wall-related stress. These findings are expected to contribute to an improved understanding of the pathogenesis of drug-resistant M. tuberculosis infections.